Correction: Long-range corrected density functional through the density matrix expansion based semilocal exchange hole. Issue 39 (27th September 2019) - Patra, Bikash; Jana, Subrata; Samal, Prasanjit
Abstract : Correction for 'Long-range corrected density functional through the density matrix expansion based semilocal exchange hole' by Bikash Patra et al., Phys. Chem. Chem. Phys., 2018, 20, 8991–8998.